2020
DOI: 10.1371/journal.pone.0229871
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of menstruation and fertility among adults in rural Western Kenya: Gaps and opportunities for support

Abstract: An understanding of menstruation and its relationship to fertility can help women know the gestational age of any pregnancies, and thus identify preterm births. It can also help women avoid unintended pregnancies. However, little is known about women, and especially men's, menstruation and fertility knowledge, outside of research on adolescent girls and stigma, and in low and middle income countries (LMIC). Additionally, little is known about practices surrounding the tracking of menstruation and fertility, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Our study findings support similar findings from other LMICs that note that most young women face challenges in accessing menstrual products and only learn about menstruation at menarche and even then, the information is limited and skewed by local myths and taboos [ 18 , 19 ]. These barriers then lead to feelings of isolation, shame, and fear that negatively inform how young women experience menstruation over time [ 3 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our study findings support similar findings from other LMICs that note that most young women face challenges in accessing menstrual products and only learn about menstruation at menarche and even then, the information is limited and skewed by local myths and taboos [ 18 , 19 ]. These barriers then lead to feelings of isolation, shame, and fear that negatively inform how young women experience menstruation over time [ 3 ].…”
Section: Discussionsupporting
confidence: 90%
“…We found that nearly all of our study participants reported knowledge improvements in areas such as the menstrual cycle (89.0%) and pregnancy health (84.6%). This is of particular relevance given the low level of health literacy among adolescents and women about their reproductive health as reported in multiple studies [15,16,19,21,54]. These results are also in line with a study independently conducted by Karasneh at el.…”
Section: Knowledge and Health Improvements Among Flo App Userssupporting
confidence: 88%
“…There is a big knowledge gap among adolescent girls and adult women, especially in low and middle income countries, about menstrual cycle health [15,16], fertility [15,17], healthy pregnancy [18] and overall women's health and wellbeing [19][20][21]. A North Indian study has found that only 31% of respondents reported the right definition of the menstrual cycle [16].…”
Section: Introductionmentioning
confidence: 99%
“…This may explain results from the Pakistan site where almost 84% of women have no formal education. A recent qualitative study of 45 men and women in rural Western Kenya reported ‘high levels of misinformation about menstruation and fertility’ and misconceptions regarding the duration of pregnancy 25. Calendar literacy appears to vary by site 26.…”
Section: Discussionmentioning
confidence: 99%